Pentingnya Apologetika Menrut 1 Petrus 3:15 bagi Penginjilan - Lucky Antonio (Sekolah Tinggi Teologi Kerusso Indonesia, 2021)
Apologetics as a branch of Theology is based on the main purpose that is to bring people to maturity and spread the Gospel. Reading the Bible in a holistic way, apologetics has been executed since the very beginning of the world’s existance and apologetics was started by God Himself when He answered those who opposed Him. Appologetics has continued to the first church and up to now when proofing the truth of the Christian belief during evangelisation and even as an act of counselling. The connection between apologetics and evangelisation is quite close, as apologetics try to answer the questionings of the Chritian beliefs,which could be a direct act of evangelisation. Wilbur Smit wrote “a spoken or written accountability of what we are doing or the Truth we are believing”. Wilbur Smit believes that being accountable is part of our conviction. Very fundamental as an apologetic is that he should have a deep conviction and sanctifies Christ in his life. This is a key factor, because the presuppostion here is that the Jesus Christ is Lord of the thoughts of an apologetic. The apologetic arguments should be towards the Lordship of Jesus Christ and wisdom of God and founded on the fear of the Lord. Foolishnes of unbelief is not to be exposed for apologetic is as neutral as other human activity. Any apologetic argument should have the Truth of God as the presupposition. Abstrak Dasar pikir inilah apologetika sebagai cabang ilmu teologia mempunyai tujuan utamanya adalah mendewasakan umat dan memberitakan Injil. Mencermati Alkitab secara holistik, aplogetika sudah diterapkan sejak keberadaan dunia dan apologetika diawali oleh TUHAN sendiri dalam memberi jawaban kepada para penentang-Nya. Kegiatan apologetika terus berlanjut sampai pada gereja awal sampai sekarang ini sebagai kegiatan menyatakan kebenaran keyakinan Kristen seperti di dalam kegiatan penginjilan bahkan sampai kepada tindakan konseling. Relasi apologetika dan penginjilan mempunyai keterikatan yang erat. Keterikatan ini tampak dari jawaban atas pertanyaan iman Kristen (apa yang diyakini) yang adalah sebuah penginjilan secara langsung. Wilbur Smit menuliskan “suatu Pertanggungjawaban lisan atau suatu uraian lisan untuk mempertanggungjawabkan apa yang kita telah lakukan atau kebenaran yang kita percayai”. Maksud Wilbur Smit adalah pertanggungjawaban adalah bagian dari apa yang diyakini. Sebuah hal yang mendasar yang harus diketahui seorang apologis adalah harus memiliki keyakinan penuh dan menguduskan Kristus di dalam hidupnya. Hal ini penting karena presuposisi Tuhan Yesus Kristus sebagai Tuhan dalam pikiran seorang apologis adalah dasar utama. Argumentasi apologis harus berpresuposisikan ke-Tuhanan Yesus Kristus dan bijaksana berdasarkan takut akan Tuhan. Kebodohan yang tidak percaya tidak dipertunjukkan, karena argumentasi apologetika tidak lebih netral dari pada aktivitas manusia yang lain. Dalam argumentasi apologetika harus berpresuposisikan kebenaran Allah.